Vocal fold insufficiency: medialization laryngoplasty vs calcium hydroxylapatite microspheres (Radiesse Voice®). (March 2013) - Cantillo-Baños, Enrique; Jurado-Ramos, Alfredo; Gutiérrez-Jódas, José; Ariza-Vargas, Leopoldo
Abstract Conclusion: The choice of technique will depend on the glottic gap observed by stroboscopy, the alteration of the Voice Handicap Index (VHI) and the recorded values of harmonics-to-noise ratio (HNR), jitter and shimmer, and the general health, age and underlying pathology. There are statistically significant differences between the values of VHI, shimmer and jitter in favour of those cases operated on within 6 months of diagnosis. Alternatives are discussed. Objectives: This study analysed and compared the functional, morphological and acoustic results, after surgery, through the techniques of medialization thyroplasty and infiltration of biomaterials to correct incomplete closure of the glottis. Methods: A total of 21 patients with dysphonia due to vocal fold insufficiency (13 women and 8 men) and ages ranging between 30 and 65 years (mean age 40.84, SD 12.5) were evaluated. The material used for augmentation surgery consisted of calcium hydroxylapatite microspheres. Measurements (VHI, jitter, shimmer and HNR) were performed before surgery and at 6 and 24 months post-intervention. Results: Overall, statistically significant differences were observed relating to measurements (p < 0.01) and surgical techniques (p < 0.05) analyzed. In particular, these differences were located in pairs pre-surgery – 6 months post-surgery and pre-surgery – post 24 months, in the four variables, and between the two techniques used in jitter (p = 0.008), HNR (p = 0.045) and VHI (p = 0.035).